Design and experimental validation of a novel compliant micro-positioning stage with nonlinear stiffness - Wang, Wei; Zheng, Jinchuan; Man, Zhihong; Wang, Hai; Chen, Xiaoqi; Chen, Yuan (Precision engineering, 2025)
This article presents a novel design of a piezoelectric actuated stage with variable nonlinear stiffness to achieve active suppression of residual vibrations in response to a step input command. In the stage design, a nonlinear stiffness mechanism with four leaf-shaped compliant legs is proposed, which possesses a more significant and rapid stiffness variation with respect to output displacement than traditional linear stiffness mechanisms. The analysis of the proposed stage design is established on the basis of large deformation theory of beams and analysed by using the pseudo-rigid method. In addition, the response surface method is employed in multi-objective optimization for the key design parameters of the stage. The static and dynamic performance of the stage is evaluated by finite element analysis. Lastly, experiments were conducted on a real prototype of the micro-positioning stage. The experimental results verify that the proposed stage can achieve a continuously adjustable displacement amplification ratio from 3.6 to 10.8 and its first natural frequency from 208 to 251Hz owing to the variable stiffness. The results also demonstrate that the stage can achieve self-suppression of the residual vibrations under a step input signal to the piezoelectric actuator. •A novel compliant micro-positioning stage with tunable nonlinear stiffness is proposed and analysed.•The stage features a continuously adjustable displacement amplification ratio and natural frequency.•Finite element analysis and experimental results validate the effectiveness of vibration suppression.